Effect of formulas of titanoxide compositions on the photovoltaic characteristics of solar cells - Aimukhanov, A.K.; Ibrayev, N.Kh.; Serikov, T.M. (Pleiades Publishing, 2016)
The effect the chemical composition of semiconductor titanium compositions (titanium pastes) has on the photovoltaic characteristics of dye-sensitized solar cells is investigated. It is established that the efficiency of solar energy conversion by a photovoltaic cell made with Ti-nanooxide D paste is 5.3%, while that of one made with Degussa P25 paste is 4.7%. These data correlate with the specific surface and sorption ability of semiconductor films.
Keywords: photovoltaics; solar cell; titanium dioxide; dye